An analysis of bibliometric data exploring factors affecting research capacity amongst HCPC registered radiographers in England. (October 2019) - Agwa, U.; Whiting, C.
Abstract: Introduction: Pre-existing studies argue, radiographers are "apathetic" when it comes to research. However, labelling everyone as such seems a gross simplification of a multifaceted issue; especially as current evidence tends to err towards the anecdotal, subjective or is compared to similar professions. Considering this, the SCoR periodically issues a Research Strategy, recognising the necessity to embed/improve research-capacity across all levels of the profession. The aim of this study is to ascertain factors characteristically influencing research-capacity amongst HCPC-registered radiographers in England. Methods: A purposeful sample of 5 years' bibliometric data from the journal 'Radiography.' A critical and thematic analysis followed based on current peer reviewed journals and grey literature. Results: Of 374 eligible articles and 143 research-active authors (published 2 + articles), collaborations prominently featured (74.9%) across 19 international partnerships. HCPC registrants in England were principal investigator(s) in 49.20% of cases and registrants affiliated with the journal/publisher generally published more than non-affiliates. Preferred topic-areas included 'Education & Research' and 'Technical Practice.' Males published more than females (M = 5.13/F = 3.45). Average length of practice equalled 22.93 years. Outputs mostly originated from HEIs (62.07%), but contributions varied (mean = 10.05/std.deviation = ±17.09); modestly correlating high-REF scoring HEIs (r = 0.330); however, regional workforce ratio(s) proved the strongest indicator (r = 0.601). Conclusion: No "one-size-fits all" approach to research-capacity applies; multiple variables affect capacity/activeness. Many seem contingent on extrinsic factors e.g. regional locale, organisational type and culture/support. Personal/professional influences included career status, length of qualification and gender. Future strategies may benefit from refinement; mindful of the dynamics influencing the heterogeneity of the current workforce. Recommendations are that future strategies/studies may benefit from more specific targeting. Highlights: Radiography research is still emergent. Many factors impact the research capacity. Future strategies may need to reduce barriers.